1996
DOI: 10.1111/j.1151-2916.1996.tb08090.x
|View full text |Cite
|
Sign up to set email alerts
|

Surface and Internal Crystallization in Glasses as Determined by Differential Thermal Analysis

Abstract: A differential thermal analysis (DTA) method has been developed that identifies and distinguishes surface and internal (volume) crystallization in glasses. This method is fast, convenient, and requires only a small quantity of sample, ∼500 mg, to identify the dominant crystallization, surface versus internal, in the glass. In this method, either the maximum height of the DTA crystallization peak, (δT”)p, or the ratio T2p/(ΔT)p, where Tp is the temperature at (δT)p and (ΔT)p the peak half width, is plotted as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(60 citation statements)
references
References 7 publications
4
55
0
1
Order By: Relevance
“…Table 2 lists the percentages of elements measured on the basis of EDX analyses. Ray et al [19] had studied the crystallization behavior of glass using DTA. The results obtained in our work suggested that the nucleation was largely controlled by the surface nucleation, which was consistent with what has been observed by Ray et al [19].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 lists the percentages of elements measured on the basis of EDX analyses. Ray et al [19] had studied the crystallization behavior of glass using DTA. The results obtained in our work suggested that the nucleation was largely controlled by the surface nucleation, which was consistent with what has been observed by Ray et al [19].…”
Section: Resultsmentioning
confidence: 99%
“…Ray et al [19] had studied the crystallization behavior of glass using DTA. The results obtained in our work suggested that the nucleation was largely controlled by the surface nucleation, which was consistent with what has been observed by Ray et al [19]. Figure 4a, b show the XRD patterns for BST glassceramics prepared by powder sintering and melt casting, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…With increasing surface (decreasing particle size), the crystallization temperature decreases, indicating that the crystallization of the diopside phase occurs preferentially at the surface. This crystallization behavior has been studied by Ray et al [18] in the thermal analysis of glasses.…”
Section: Thermal Analysismentioning
confidence: 86%
“…However, in the non-phase-separated samples of x = 9 and 18, the apparent activation energy increased with the decrease of their granular sizes. In this case of surface crystallization, the rate of crystallization normally increases with the decrease of the granular size of the glass, 25) because the large surface area of the small particles enhances surface crystallization due to the increase in the heterogeneous nucleation points at their surfaces. In other words, the surface crystallization is dominant for the small particle sample and the bulk crystallization is dominant for the larger particle sample for the non-phaseseparated glasses.…”
Section: Crystallization Behavior Under Non-isothermal Heat Treatmentmentioning
confidence: 99%